An Analysis on the Relationship between the Number of Particles and the Volume by Using the Gas Kinetic Theory Model - Nurazmi Nurazmi; A. Taufik Hidayat Prayuda; Nurul Ainun Maudil Khawair; Harni Harni; Surya Sutriana; Riska Riska (Universitas Muhammadiyah Makassar, 2020)
This study aims at finding out the relationship between the number of particles and the volume by using the gas kinetic theory model. In this study, the data collection was conducted three times employing different particle numbers, namely 10 particles, 20 particles and 30 particles group. During the data collection process, the scale reading of the load height was done when the load collision has been going on for 20 seconds. Based on the observations, it can be obtained that the more the number of particles, the greater the volume. The graph analysis also reveals that the slope of the three graphs varies. Graph 4.1 and graph 4.2 share the same slope that is 0.1, while the slope of graph 4.3 is 0.095. The slope of the graph illustrates that once the number of particle increases, the position of the piston will also go up. In other words, it can be said that the changes in the position of the piston (v) is directly proportional to the number of particles (n).Keywords: Kinetic Theory Of Gases, Volume, Piston Position, ParticlePenelitian ini bertujuan untuk mengetahui hubungan jumlah partikel dengan volume menggunakan model teori kinetic gas. Pada penelitian ini, pengambilan data dilakukan sebanyak tiga kali dengan jumlah partikel yang berbeda-beda yaitu 10 partikel, 20 partikel dan 30 partikel. Pada proses pengambilan data yang dilakukan, pembacaan skala ketinggian beban dilakukan ketika penumbukan beban telah berlangsung selama 20 detik. Berdasarkan hasil pengamatan diperoleh bahwa semakin banyak jumlah partikel maka volumenya akan semakin besar pula. Dari hasil analisis grafik diperoleh kemiringan pada grafik 4.1 yaitu 0,1, grafik 4.2 diperoleh kemiringan 0,1 dan grafik 4.3 diperoleh kemiringan 0,095. Kemiringan grafik menggambarkan bahwa setiap pertambahan partikel bertambah pula kedudukan piston atau dapat dikatakan hubungan antara perubahan kedudukan piston (v) berbanding lurus dengan jumlah partikel (n).Kata kunci: Teori Kinetik Gas, Volume, Kedudukan Piston, Partikel